حول فعالية الوساطة كإجراء بديل لتسوية المنازعات الإدارية: "دراسة نقدية" - أوكيل ., محمد أمين (University of Eloued جامعة الوادي, 2021)
تهدف هذه الدراسة لمقاربة ومفهوم الوساطة في المادة الادارية بكونها أداة جديدة لحل النزاعات الإدارية استحدثها المشرع في قانون رقم 08-09 المتعلق بالإجراءات المدنية والإدارية. سمحت الدراسة بتبيان أسس التكريس القانوني لإجراء الوساطة في القانون الوطني، وبتقييم مدى فعاليته في حل النزاعات الادارية. وهذا ما تبيّن من خلال مجموعة الحدود والنقائص التي توصلت إليها الدراسة في الختم والمتعلقة بالقيود المرتبطة بذاتية الاجراء من جهة وبالعراقيل المتصلة بدور الوسيط ومجال تدخله من جهة ثانية. Abstract: This study aims to conceive mediation in administrative matters as a new mechanism for resolving administrative disputes that the legislator introduced in Law No. 08-09 relating to civil and administrative procedures. The study also made it possible to clarify the legal foundations of mediation in Algerian law and to assess its effectiveness in the resolution of administrative disputes. This has been demonstrated through all the limits and gaps linked to the restrictions linked to the nature of this mechanism on the one hand, and to the obstacles linked to the role of the mediator on the other
On the effectiveness of Mediation as an Alternative Mechanism for Administrative Dispute Resolution: A Critical Study
مقال
Keywords: الوسيط ; الوساطة القضائية ; المادة الادارية ; النزاع الاداري ; التسوية القضائية؛; Mediator, judicial mediation, disputes, administrative article